Zirconium Oxycarbide: A Highly Stable Catalyst Material for Electrochemical Energy Conversion. Issue 22 (10th July 2019) - Shakibi Nia, Niusha; Hauser, Daniel; Schlicker, Lukas; Gili, Albert; Doran, Andrew; Gurlo, Aleksander; Penner, Simon; Kunze‐Liebhäuser, Julia
Abstract: Metal carbides and oxycarbides have recently gained considerable interest due to their (electro)catalytic properties that differ from those of transition metals and that have potential to outperform them as well. The stability of zirconium oxycarbide nanopowders (ZrO0.31 C0.69 ), synthesized via a hybrid solid‐liquid route, is investigated in different gas atmospheres from room temperature to 800 °C by using in‐situ X‐ray diffraction and in‐situ electrical impedance spectroscopy. To feature the properties of a structurally stable Zr oxycarbide with high oxygen content, a stoichiometry of ZrO0.31 C0.69 has been selected. ZrO0.31 C0.69 is stable in reducing gases with only minor amounts of tetragonal ZrO2 being formed at high temperatures, whereas it decomposes in CO2 and O2 gas atmosphere. From online differential electrochemical mass spectrometry measurements, the hydrogen evolution reaction (HER) onset potential is determined at −0.4 VRHE . CO2 formation is detected at potentials as positive as 1.9 VRHE as ZrO0.31 C0.69 decomposition product, and oxygen is anodically formed at 2.5 VRHE, which shows the high electrochemical stability of this material in acidic electrolyte. This peopwery makes the material suited for electrocatalytic reactions at anodic potentials, such as CO and alcohol oxidation reactions, in general. Abstract : Stable nanopowders : The electrochemical behavior of ZrO0.31 C0.69 is studied in acidic electrolyte over a wide potential range. The onset potential of the hydrogen evolution reaction is −0.4 VRHE . CO2 formation due to anodic decomposition of ZrO0.31 C0.69 is detected at 1.9 VRHE, accounting for the oxycarbide's high electrochemical stability. Thus, the oxycarbide is generally suited for anodic electrocatalytic reactions, such as CO and alcohol oxidation.